Placental changes in a group of full-term newborns with hypoxic-ischemic encephalopathy - Andreea Calomfirescu-Avramescu; Luminita Ceauselu; Vlad Dima; Mihaela Demetrian; Anca Balanescu; Paul Balanescu; Ioan Gherghina (Amaltea Medical Publishing House, 2022)
Objectives. The aim of this study was to present and describe specific macroscopic and microscopic placental findings in patients with hypoxic-ischemic encephalopathy (HIE). Materials and methods. We conducted an observational prospective study which included 84 patients diagnosed with HIE and had available placental histopathological examination. HIE diagnosis was performed according to Sarnat Score. Both macroscopical and microscopical placental lesions were identified. Patients were divided into 2 groups according to the presence of placental lesions. Outcomes. Placental lesions were associated with HIE. Patients with both HIE and placental lesions had lower pH value (p <0.001) and lower Apgar scores (p=0.001). Conclusion. Antenatal placental lesions are present in full-term infants with encephalopathy and seem to define exactly one of the causes of this syndrome.